Paradigmas de desenvolvimento de software: comparação entre abordagens orientada a eventos e orientada a notificações - Xavier, Robson Duarte (2014)
The objective of this work was comparing two distinct software development paradigms, namely, the emerging Notification Oriented Paradigm (NOP) and Event-driven Paradigm (EDP). Objectives, methods and tools are presented and two case studies are described (the first with three scenarios) and their respective reflexions, experiments and data. The comparison is theoretical and practical, correlating structural characteristics in NOP and EDP in a common taxonomy, therefore comparing them in code complexity (number of lines of code, closures and tokens) and comparing them with respect to performance (response time and total execution time), by building and instrumenting the case studies in both paradigms. As results, was identified that NOP, despite being inspired by events, using notifications on its execution model, shows conceptual differences from EDP. Moreover, in the present state of technology, NOP has response time during execution comparable to EDP implementation, and NOP has performance that adapts to software context (faster response times when events should be ignored and higher response times when executing more actions per event. With specific NOP language and compiler (LangNOP) data shows linear response times comparable to the EDP.